Indonesia's Interests and Challenges in Joining Brics - Roby Arman Myajaya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study analyzes the international ramifications of the Russia-Ukraine conflict, focusing on its economic, political, and security dimensions. The conflict has disrupted global trade, particularly in the energy and agricultural sectors, leading to inflation and price volatility worldwide. Politically, it has shifted global alliances, with Western countries strengthening NATO and imposing sanctions on Russia, while some nations have chosen strategic neutrality. In terms of security, the conflict has exacerbated global tensions and driven increased military expenditures across major powers. The research employs a qualitative approach, using a literature review method to analyze both primary and secondary sources, including policy documents, academic journals, and international reports. The study identifies key challenges such as food security, energy shortages, and the polarization of international relations. The paper suggests that strengthening multilateral diplomatic efforts is crucial for mediating the conflict and mitigating its global economic and security consequences. In conclusion, the study argues that addressing the global impact of the Russia-Ukraine conflict requires strategies that